Epidemiology and Estimated Cost of Surgeries for Carpal Tunnel Syndrome Conducted by the Unified Health System in Brazil (2008–2016) - Magalhães, Marcelo José da Silva de; Fernandes, Jeffet Lucas Silva; Alkmim, Mateus Silva; Anjos, Evandro Barbosa dos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Objective To define the epidemiological aspects and estimated costs of surgeries performed by the Brazilian Unified Health System (SUS, in the Portuguese acronym) for the treatment of carpal tunnel syndrome (CTS) in Brazil between 2008 and 2016.Materials and Methods Documentary study, with data from the Informatics Department of the SUS (DATASUS, in the Portuguese acronym), about the absolute number and incidence of admissions, the total and mean length of stay (in days), the total expenses, and the hospital and professional services expenses in the surgical treatment of CTS.Results During the period studied, there were 82,123 hospitalizations for surgery, with a 62% increase from 2008 to 2015, accompanied by an increase in the values of professional services. The incidence and the absolute number of procedures were higher in the South and Southeast regions. The North region presented the lowest expenses, absolute number, and incidence of admissions, as well as the longer mean length of stay. The mean length of stay decreased from 1.2 days in 2008 to 0.7 day in 2016. The expenses totaled BRL 29,463,148.80 during the period studied. After 2011, professional services became the largest portion of the total expenses. Hospital expenses corresponded to 52.49% of the expenditure in 2008, and to 36.24% in 2015, while professional expenses received the largest investment compared with the total amount expended in 2012.Conclusion The present study was not consistent with the international literature regarding epidemiological data and cost estimates. Brazil presented a disparity between absolute numbers and annual incidence of admissions and length of stay. Future researches can assess variables that have influenced these results, as well as contribute to public interventions aimed at the improvement of health care.
Keywords: epidemiology; carpal tunnel syndrome/surgery; median nerve; health expenditures